Research Programs of I. Lakatos in the Context of the Information Society - O. E. Baksansky; I. A. Emelin (Сеченовский вестник, 2015)
The article attempts to describe the concept of development and change of research programs of the hungarian scientist Imre Lakatos, to defi ne features of his scientifi c methodology and his views on the history and philosophy of science in the context of the information society.